The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1128/jvi.75.9.4321-4331.2001
|View full text |Cite
|
Sign up to set email alerts
|

Global Impact of Influenza Virus on Cellular Pathways Is Mediated by both Replication-Dependent and -Independent Events

Abstract: Influenza virus, the causative agent of the common flu, is a worldwide health problem with significant economic consequences. Studies of influenza virus biology have revealed elaborate mechanisms by which the virus interacts with its host cell as it inhibits the synthesis of cellular proteins, evades the innate antiviral response, and facilitates production of viral RNAs and proteins. With the advent of DNA array technology it is now possible to obtain a large-scale view of how viruses alter the environment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 61 publications
8
96
0
1
Order By: Relevance
“…To our knowledge, the present study is the first demonstration of the activation of MT genes in response to an experimental viral infection in an animal model and elucidation of the molecular mechanisms for the induction process. One recent study using DNA microarray technology has identified MT-IIA as one of the genes induced in HeLa cells infected with influenza A virus (20). This study does not, however, address the molecular mechanisms of MT induction in specific tissues of organisms.…”
Section: Discussionmentioning
confidence: 89%
“…To our knowledge, the present study is the first demonstration of the activation of MT genes in response to an experimental viral infection in an animal model and elucidation of the molecular mechanisms for the induction process. One recent study using DNA microarray technology has identified MT-IIA as one of the genes induced in HeLa cells infected with influenza A virus (20). This study does not, however, address the molecular mechanisms of MT induction in specific tissues of organisms.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, Geiss et al (53) did not detect IFN-␤ mRNA itself among the up-regulated mRNAs at 4 or 8 h after infection. This implicates a cell-type-specific response to influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that production of inflammatory mediators in response to a viral infection can occur in the presence or absence of multiplication of the pathogen (22). We tested whether viral contact with the plasma membrane and/or viral penetration of the host cell was sufficient to trigger the inflammatory response.…”
Section: Comparison Of the Activation Of Bronchial Respiratory Cellsmentioning
confidence: 99%